Pengaruh Persepsi Risiko, Kemudahan, Manfaat Dan Harga Terhadap Keputusan Pembelian Sepatu (Studi Kasus Pada Mahasiswa FEB Unisma Program Manajemen Angkatan 2017 Yang Membeli Online Melalui Instagram) - Shafiah Arsyi Mu’minin; N. Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study is to find out the perception of risk, convenience, benefits and price to purchasing decisions. This study sample consists of 116 FEB University Islamic of Malang students in 2021. Method of data collection by collecting primary and secondary data. To find out the data that will be studied, this study uses how to spread questionnaires online.  The study used the SPSS version 16measurement tool to test data in the form of instrument testing, normality tests, multiple linear regression analysis, classical assumption testing, and hypothesis testing. From this study produced several conclusions that mention that variables of risk perception, convenience, benefits and prices simultaneously or together have an effect on purchasing decisions. Partially variables of risk perception, convenience, benefits and price have a significant positive effect on purchasing decisions. Keywords: Purchasing Decision, Risk Perception, Benefit, Price